Photonic Crystals: Physics and Technology - Sibilia, C. (Springer, 2017)
Introduction to photonic crystals and photonic band-gaps / Richard M. De La Rue and Sarah A. De La Rue -- Physics of slow bloch modes and their applications / Pierre Viktorovitch -- Quasi phase matching in two-dimensional quadratic nonlinear photonic crystals / Ady Arie, Nili Habshoosh and Alon Bahabad -- Harmonic generation in nanostructures: metal nanoparticles and photonic crystals / Andrea Marco Malvezzi -- Ultra-fast optical reconfiguration via nonlinear effects in semiconductor photonic crystals / Crina Cojocaru ... [et al.] -- Nonlinear optics with photonic-crystal fibres / Aleksei M. Zheltikov -- Photonic crystal and photonic band-gap structures for light extraction and emission control / Richard M. De La Rue -- Silicon-based photonic crystals and nanowires / Bozena Jaskorzynska and Lech Wosinski -- Near Infrared optical characterization techniques for photonic crystals / Romuald Houdré -- Characterization techniques for planar optical microresonators / René M. de Ridder, Wico C.L. Hopman and Edwin J. Klein -- On SNOM resolution improvement / Tomasz J. Antosiewicz, Marian Marciniak and Tomasz Szoplik -- Photonic crystals: simulation successes and some remaining challenges / Trevor M. Benson and Peter Bienstman -- Plane-wave admittance method and its applications to modelling photonic crystal structures / Maciej Dems ... [et al.].